2012
DOI: 10.3389/fpsyg.2012.00479
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic Processing of Accented Speech Across the Lifespan

Abstract: In most of the world, people have regular exposure to multiple accents. Therefore, learning to quickly process accented speech is a prerequisite to successful communication. In this paper, we examine work on the perception of accented speech across the lifespan, from early infancy to late adulthood. Unfamiliar accents initially impair linguistic processing by infants, children, younger adults, and older adults, but listeners of all ages come to adapt to accented speech. Emergent research also goes beyond these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
104
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(112 citation statements)
references
References 146 publications
3
104
0
Order By: Relevance
“…Varying results have been reported regarding the relative benefit of training for different age groups (Cristia et al, 2012). For this experiment, it is predicted that younger adults will show higher overall speech recognition scores than older adults.…”
Section: Research Questions and Hypothesesmentioning
confidence: 94%
See 1 more Smart Citation
“…Varying results have been reported regarding the relative benefit of training for different age groups (Cristia et al, 2012). For this experiment, it is predicted that younger adults will show higher overall speech recognition scores than older adults.…”
Section: Research Questions and Hypothesesmentioning
confidence: 94%
“…These difficulties can be exacerbated in more challenging listening circumstances, such as listening to foreignaccented speech in the presence of noise (Gordon-Salant et al, 2010b). It has been suggested that this poorer performance may be related to cognitive decline associated with aging, as well as to auditory temporal processing deficits (Cristia et al, 2012).…”
mentioning
confidence: 99%
“…The ability to recognize speech in adverse listening conditions is a robust and flexible mechanism that is supported by our ability to "tune in" to unfamiliar or distorted speech (for reviews, see Samuel and Kraljic, 2009;Cristia et al, 2012;Mattys et al, 2012). Such perceptual adaptation can be defined as improved speech recognition (that is, accessing the semantic content of the speech message through perceiving the acoustic signal) as a result of exposure to an unfamiliar speech type.…”
Section: Introductionmentioning
confidence: 99%
“…Listeners' awareness of foreign accents in speech has received considerable attention in speech research for a number of years (e.g., Flege, Munro, & MacKay, 1995;Munro, Derwing, & Burgess, 2010). Less attention has been paid to the question of what a foreign accent means for language comprehension (for a recent review see, Cristia et al, 2012). How does prior language experience shape the way listeners adapt to a foreign accent?…”
Section: Introductionmentioning
confidence: 99%